2021
DOI: 10.1007/s00723-021-01383-6
|View full text |Cite|
|
Sign up to set email alerts
|

Oxygenation Status of Malignant Tumors vs. Normal Tissues: Critical Evaluation and Updated Data Source Based on Direct Measurements with pO2 Microsensors

Abstract: Immature and chaotic vascular networks with critically increased intervascular distances are characteristic features of malignant tumors. Spatial and temporal heterogeneities of blood flow and associated availabilities of O2, together with limited diffusive O2 transport, and -in some patients- anemia, obligatorily lead to tumor hypoxia (= critically reduced O2 levels) on macro- and microscopic scales. This detrimental condition, recently classified as a key hallmark of malignant growth, acts (a) as a barrier i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 109 publications
0
25
0
Order By: Relevance
“…Adding to the complexity of this challenge, cells throughout the body reside in tissue microenvironments with dramatically different O 2 levels: airway epithelial cells are exposed to 21% O 2 , whereas in mouse thymus the median recorded partial pressure of oxygen (pO 2 ) was 7.6 mmHg, which corresponds to approximately 1% O 2 ( 2 ). Even within the same organ, tissue oxygenation varies tremendously: in the kidney, pO 2 varies from 70 mmHg in the outer cortex to 10 mmHg in the inner medulla ( 3 ).…”
Section: Hypoxia-inducible Factors and Oxygen Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…Adding to the complexity of this challenge, cells throughout the body reside in tissue microenvironments with dramatically different O 2 levels: airway epithelial cells are exposed to 21% O 2 , whereas in mouse thymus the median recorded partial pressure of oxygen (pO 2 ) was 7.6 mmHg, which corresponds to approximately 1% O 2 ( 2 ). Even within the same organ, tissue oxygenation varies tremendously: in the kidney, pO 2 varies from 70 mmHg in the outer cortex to 10 mmHg in the inner medulla ( 3 ).…”
Section: Hypoxia-inducible Factors and Oxygen Homeostasismentioning
confidence: 99%
“…Indeed, even preinvasive lesions, such as ductal carcinoma in situ of the breast, may contain regions of necrosis ( 23 ) in which O 2 availability is insufficient to maintain cell viability ( 24 ). In human breast cancers, measured diffusion distances for O 2 ranged from 70 μm at arterial inflow to 30 μm at venous outflow ( 3 ), meaning that O 2 rapidly becomes limiting as distance from the nearest blood vessel increases. Patients with cervical cancer, head/neck cancer, or soft-tissue sarcoma who have intratumoral pO 2 less than 10 mmHg have significantly decreased survival ( 22 ).…”
Section: Mechanisms Of Hif Activation In Cancermentioning
confidence: 99%
“…It has also been demonstrated that positronium lifetime changes inversely to the oxygen concentration in organic liquids [36,37] and can be considered a biomarker of hypoxia [14]. The partial pressure of oxygen in neoplastic tissues is lower by more than 10 mmHg with respect to healthy tissues of the same organ, and for the pancreas, the difference is as high as 50 mmHg [38]. In order to distinguish such an oxygen pressure difference, an orthopositronium lifetime resolution of about 2 ps is required [14].…”
Section: Positronium As a Biomarker Of Cancer And Hypoxiamentioning
confidence: 99%
“…In breast cancer, oxygen tension ranges from 2.5 to 28 mm of mercury (Hg) which is in stark contrast with the 65 mm Hg in normal human breast tissue [ 18 ]. Oxygen tension values of less than 10 mm Hg are linked to an increasing risk of metastasis, thus, indicating that hypoxic breast cancers show more aggressive behavior [ 19 ]. While the ability of hypoxia to influence the metastatic cascade is recognized, the mechanism behind it is incompletely understood.…”
Section: Hypoxia In Breast Cancermentioning
confidence: 99%